1996
DOI: 10.1111/j.1600-0765.1996.tb00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein composition of whole and parotid saliva in healthy and periodontitis subjects

Abstract: Cystatins are physiological inhibitors of cysteine proteinases and they are widely distributed in human tissues and body fluids including saliva. We previously reported an increased cystatin activity in whole saliva of gingivitis and periodontitis subjects. Based on this result we decided to investigate the type and origin of cystatins involved in this increased cystatin activity by collecting both whole and parotid saliva of 25 healthy and 30 periodontitis subjects. Saliva samples were quantified for cystatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
100
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 41 publications
9
100
0
1
Order By: Relevance
“…Our study is in accordance with other studies which showed an increase in amylase levels in patients with gingivitis and periodontitis [5,13,16,17].…”
Section: Collection Of Salivasupporting
confidence: 82%
See 2 more Smart Citations
“…Our study is in accordance with other studies which showed an increase in amylase levels in patients with gingivitis and periodontitis [5,13,16,17].…”
Section: Collection Of Salivasupporting
confidence: 82%
“…The increased protein levels in our study in the test groups could be due to the inflammatory process that activates the sympathetic system to enhance the synthesis and secretion of some proteins (as evidenced by increased amylase levels) thereby increasing the protective potential of saliva against the diseases [12,13].…”
Section: Collection Of Salivamentioning
confidence: 99%
See 1 more Smart Citation
“…There is some discordance among the reported levels of cystatin mRNAs, protein concentrations, and cystatin activity (Henskens et al, 1996a,c;Dickinson et al, 2002), suggesting a contribution of post-translational and post-secretion events (such as N-terminal processing) to overall inhibitory capacity. Also, for parotid Table 2 in Henskens et al (1996a).…”
Section: (Ii) Papain-like Cp Inhibitory Activities Of Human Type 2 Cymentioning
confidence: 99%
“…A possible role for cystatin C in bone resorption in vitro was investigated by Lerner and Grubb (1992) by analyzing the parathyroid hormone stimulated release of 45 Ca and 3 H from prelabeled mouse calvarial bones. Using recombinant cystatin C they showed a significant reduction in the release of 45 Ca and 3 H. 1991Barka etal., 1992Keppler etal., 1994Henskens era/., 1994,1996bBabnik etal., 1988Skaleric et a/., 1989Buttle et a/., 19901991Warfelefa/.,19871991Chapman etal., 1990 Lenarcic ef a/., 1988a Bollengier ef a/., 1987;MacPherson.1965Lofbergefa/,,1980 Grubber a/., 1984 Ghiso era/., 1986 Löfberg and Grubb, 1979Brzinefa/,,1984Kabandaefa/,,1994Lerner and Grubb, 1992Korantefa/,,1986Collins and Grubb, 1991Bjorckefa/.,1990Bjorckefa/,,1989 …”
Section: Inflammatory Diseasesmentioning
confidence: 99%